PENGARUH PELAYANAN DAN FASILITAS TERHADAP KEPUASAN PELANGGAN BUS TRANS PADANG - Masrin, Indra; Hasibuan, Elis (MENARA EKONOMI, 2019)
This study aims to determine the effect of service on the satisfaction of Trans Padang Bus customers, the effect of facilities on Trans Padang Bus Customer Satisfaction and the Effect of Services and Facilities on Trans Padang Bus Customer Satisfaction. The method used in this study is Quantitative which was examined by questionnaire. The sampling technique uses accidental sampling with a sample size of 100. Data were analyzed through validity test, reliability test, classic assumption test, normality test, multicollinearity test, heteroscedasticity test, autocorrelation test, descriptive statistical analysis, multiple regression analysis, partial test (t) , simultaneous test (f), and coefficient of determination. The results showed that the Service had a significant effect on the satisfaction of Trans Padang Bus customers or 0.031 <0.05 and the Facility Significantly Influenced Trans Padang Bus Customer Satisfaction or 0.021 <0.05 partially. Services and facilities have a significant effect on the satisfaction of Trans Padang Bus Customers or 0.040 <0.05 simultaneously. Trans Padang Bus Services and Facilities should be improved. Improvements can be made by maintaining existing and improving adequate Services and Facilities so that Trans Padang Bus Customers are satisfied when using Trans Padang Bus services.Keywords: Services, Facilities, Customer Satisfaction